The effect of an ionophore, essential oils and a probiotic on the rumen and jejunal microbiome of South African Bonsmara cattle raised under feedlot conditions - Van Marle-Koster, Este (University of Pretoria, 2023)
Thesis (PhD (Animal Science))--University of Pretoria, 2022.